THERAPY CENTER EMPOWERS INTELLECTUALLY DISABLED THROUGH ACTIVITY-BASED APPROACH IN BOGOR REGENCY - Bisyarah, Intan Safa (Architecture Department, Engineering Faculty, Universitas Diponegoro, 2024)
The purpose of writing this final project is as a basis for planning and designing therapy facilities for the intellectually disabled based on activity scenarios. Mental retardation, also known as intellectually disabled, is a person with special needs who has intellectual, physical, emotional and social retardation who requires special treatment in order to develop optimally. Currently, the number of intellectually disabled people in Indonesia is 1,389,614 people. The level of social awareness for people with special needs in Indonesia is still low. There were 987 cases of violence experienced by children with special needs that occurred in 2021, 264 of which occurred in boys and 764 occurred in girls. Therefore, a therapy center is needed to provide attention or assistance to children with special needs, especially the intellectually disabled, so that they develop a sense of self-confidence and when socializing with society, children do not feel isolated or shunned in society. The discussion method for this final project uses a descriptive method by collecting, describing and analyzing secondary data obtained as a basis for planning and designing, then making decisions from the data that has been collected and studied. The data collection methods used are literature studies, standard studies, field and digital observations, as well as comparative and exploratory studies. The exploration method used is to design scenarios for intellectually disabled therapy activities based on topological space. This design is located in Gunung Putri District, Bogor Regency, precisely in Tlajung Udik. This final project is entitled